Thiol/disulphide homeostasis in Helicobacter pylori infected patients - Baykan, Ahmed Ramiz; Biçer, Cemile; Gerçeker, Emre; Erel, Özcan; Cerrah, Serkan; Albayrak, Bülent; Utlu, Mustafa; Kargılı, Ayşe (The European Research Journal, 2019)
Objectives: The aim of the study was to evaluate the oxidative stress level in patients, diagnosed with Helicobacter pylori infection, using a novel marker (thiol/disulphide homeostasis) and to compare the level in infected individuals with that in healthy volunteers. Methods: A total of 60 patients diagnosed with gastritis, erosive gastritis or ulcer by endoscopy were included and biopsied. The 30 patients diagnosed with H. pylori and 30 healthy individuals were enrolled. Medical histories, physical examination results, body mass index (BMI), hemogram, free triiodothyronine (FT3), free thyroxine (FT4), thyroid stimulating hormone (TSH), urea, creatinin, aspartate aminotransferase (AST), alanine aminotransferase (ALT), albumin, total cholesterol, triglycerides, high density lipoprotein (HDL), low density lipoprotein) LDL and thiol/disulphide levels obtained in the study groups were compared. Results: There was no significant difference between the total thiol, native thiol, disulphide/native thiol and dissulphide/total thiol ratios of the patient and control group. When the H. pylori patients were stratified by endoscopic evaluation as having mild (superficial gastritis or normal appearance) or severe (ulcer or erosive areas) symptoms, there were significant differences in disulphide, disulphide/native thiol, disulphide/total thiol and native thiol/total thiol levels. We also observed BMI and the total, native thiol levels of H. pylori patients were inversely related.( r: 0.562, p = 0.001; r: 0.0552, p = 0.002). Conclusions: Thiol/disulphide homeostasis is likely to differ with both duration and severity of H. pylori infection. Further investigations are needed to investigate the effect of H. pylori on oxidative stress.